2020
DOI: 10.5713/ajas.19.0736
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genotypes on macronutrients and antioxidant capacity of chicken breast meat

Abstract: Objective: The increasing consumer awareness of food, which can provide health benefits and potentially aid disease prevention, has become the driving force of the functional food market. Accordingly, the aim of this study was to investigate the effects of chicken genotype on the macronutrient content, bioactive peptide content, and antioxidant capacity within different breast meat.Methods: In this experiment, three genotypes of chicken, Thai indigenous, black-boned, and broiler (control), were reared with com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 33 publications
1
23
0
1
Order By: Relevance
“…In this way, they obtained that the Thai indigenous genotype had breast meat with the highest antioxidant capacity compared to the other genotypes. Furthermore, in this study Lengkidworraphiphat et al [ 39 ] concluded that the DPPH • assay was more selective than ABTS •+ test in relation to proton donors. Additionally, they observed that the results of the FRAP and DPPH • tests were consistent with each other.…”
Section: Applications Of Antioxidant Assays In Meat and Meat Productsmentioning
confidence: 54%
See 3 more Smart Citations
“…In this way, they obtained that the Thai indigenous genotype had breast meat with the highest antioxidant capacity compared to the other genotypes. Furthermore, in this study Lengkidworraphiphat et al [ 39 ] concluded that the DPPH • assay was more selective than ABTS •+ test in relation to proton donors. Additionally, they observed that the results of the FRAP and DPPH • tests were consistent with each other.…”
Section: Applications Of Antioxidant Assays In Meat and Meat Productsmentioning
confidence: 54%
“…Moreover, the extracting solvent to be utilized also differs according to the work. For example, Perna et al [ 52 ] and Simonetti et al [ 38 ] used 0.05 M phosphate buffer to extract the antioxidant compounds, while other authors utilized 80% methanol [ 35 ], 100% methanol [ 14 , 42 ], water and chloroform [ 27 ], 0.01 N hydrochloric acid [ 39 ], and 100% ethanol [ 41 , 53 ] in meat or its derivatives. Additionally, the operations followed in the extraction of antioxidant compounds also differ according to the research consulted.…”
Section: Determination Of Antioxidant Capacity In Meat and Meat Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tian et al [ 23 ] found that the carnosine content observed in the breast meat of Black-Bone Silky Fowl—a unique breed of chicken native to South China—was approximately 1.8-fold higher than that observed in the meat of White Plymouth Rock reared under the same conditions ( p < 0.01). A recent study has reported significantly higher carnosine content in the breast muscles of Thai indigenous slow-growing chickens than in broiler chickens [ 24 ]. KRC is a crossbred chicken with Thai indigenous chickens and has a slow growth rate.…”
Section: Discussionmentioning
confidence: 99%